SERPIHAN PEMIKIRAN HUKUM ISLAM DALAM MAZHAB SYIAH - Muhammad Siddiq Armia (Universitas Islam Negeri Ar-Raniry, 2017)
In the begining, Sect of Shiah was born from political background, then became part of Islamic Jurisprudence. The sect of Shiah has emerged from the differen perspective of seeing Chalif of Ali Bin Abi Thalib. From the extrem perspective of Shia, they claim that Jibril as the angel revealition has made a serious mistake, because of delivering revealition to Muhammad instead of Chaliph Ali bin Abi Thalib. Thus, not all of Sect of Shiahs’ are misleading, some of them still have a right path. This article will explore the Islamic legal thought in the perpective of Shia sects, to get a clear point of view on them and to prevent misunderstanding of Shia sects in the Islamic society. Keywords: Sects, Shia, Misleading Thought